1989
DOI: 10.1128/mcb.9.10.4323
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of gene expression by nuclear and cytoplasmic rel proteins.

Abstract: Transcriptional activation of gene expression by oncogenic proteins can lead to cellular transformation. It has recently been demonstrated that the protein encoded by the v-rel oncogene from reticuloendotheliosis virus strain T can transactivate gene expression from certain promoters in a cell-specific manner. We have examined the cytological location, transforming properties, and transactivation properties of proteins encoded by chimeric turkey v-rel/chicken c-rel genes. We found that whereas the v-rel protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
82
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 49 publications
5
82
0
Order By: Relevance
“…Together with our analysis of c-Rel mutants, these data underscore the important role of cTAD2 in the subcellular localization of Rel proteins and indicate that particular mutations in the Rel TADs can affect gene-specific expression and be a determining factor for cell transformation. Our findings agree with reports suggesting a role for c-Rel's C-terminus in its cytoplasmic anchoring and negative regulation by IkBa (Figure 4; Hannink and Temin, 1989;Capobianco et al, 1990;Diehl et al, 1993;Starczynowski et al, 2003;Iwai et al, 2005). cTAD2 mutations that dampen negative feedback by IkBa are likely to enable long-lasting activation of genes important for cell transformation, as seen for ch-IAP1 (Kralova et al, 2002).…”
supporting
confidence: 92%
“…Together with our analysis of c-Rel mutants, these data underscore the important role of cTAD2 in the subcellular localization of Rel proteins and indicate that particular mutations in the Rel TADs can affect gene-specific expression and be a determining factor for cell transformation. Our findings agree with reports suggesting a role for c-Rel's C-terminus in its cytoplasmic anchoring and negative regulation by IkBa (Figure 4; Hannink and Temin, 1989;Capobianco et al, 1990;Diehl et al, 1993;Starczynowski et al, 2003;Iwai et al, 2005). cTAD2 mutations that dampen negative feedback by IkBa are likely to enable long-lasting activation of genes important for cell transformation, as seen for ch-IAP1 (Kralova et al, 2002).…”
supporting
confidence: 92%
“…In the C-terminal 80 amino acids, no arginine or lysine is found, and 30 out of 80 residues are PEST sequences. A similar observation was also made in avian c-Rel protein (35,48).…”
Section: C-rel Degradation By Ub-pr Pathwaysupporting
confidence: 53%
“…Similar transfection studies with p50 have failed to demonstrate transcriptional activation functions (7,57,60,64). Other studies have demonstrated that both c-rel and dorsal have activation domains within the C-terminal region (12,20,26,29,30,57). In contrast, by using an in vitro transcription assay, it has been shown that the rel homology domain of p50 is capable of transcriptional activation (19,39).…”
mentioning
confidence: 87%